2004
DOI: 10.1104/pp.104.046441
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sulfate Uptake and Expression of Sulfate Transporter Genes in Brassica oleracea as Affected by Atmospheric H2S and Pedospheric Sulfate Nutrition

Abstract: Demand-driven signaling will contribute to regulation of sulfur acquisition and distribution within the plant. To investigate the regulatory mechanisms pedospheric sulfate and atmospheric H 2 S supply were manipulated in Brassica oleracea. Sulfate deprivation of B. oleracea seedlings induced a rapid increase of the sulfate uptake capacity by the roots, accompanied by an increased expression of genes encoding specific sulfate transporters in roots and other plant parts. More prolonged sulfate deprivation result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
229
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(251 citation statements)
references
References 36 publications
20
229
1
1
Order By: Relevance
“…We found that smt15-1 overaccumulates glutathione (Fig. 5A), whose elevated levels are known to suppress the SAC response (Herschbach and Rennenberg, 1994;Lappartient et al, 1999;Vauclare et al, 2002;Buchner et al, 2004). It is likely, therefore, that elevated levels of glutathione in smt15-1 strains attenuate the SAC response in -S conditions.…”
Section: Smt15 and Sac Responsesmentioning
confidence: 77%
See 1 more Smart Citation
“…We found that smt15-1 overaccumulates glutathione (Fig. 5A), whose elevated levels are known to suppress the SAC response (Herschbach and Rennenberg, 1994;Lappartient et al, 1999;Vauclare et al, 2002;Buchner et al, 2004). It is likely, therefore, that elevated levels of glutathione in smt15-1 strains attenuate the SAC response in -S conditions.…”
Section: Smt15 and Sac Responsesmentioning
confidence: 77%
“…been reported that glutathione, one of the end products of the sulfur assimilation pathway, is capable of repressing sulfur assimilation and uptake in plants (Herschbach and Rennenberg, 1994;Lappartient et al, 1999;Vauclare et al, 2002;Buchner et al, 2004). Additionally, glutathione has been shown to play a role in cell cycle progression in plants and animals (Thelander and Reichard, 1979;Menon et al, 2003;Menon and Goswami, 2007;Diaz Vivancos et al, 2010b).…”
Section: Genotypementioning
confidence: 99%
“…35,36 The inhibition in the activity of ATPS1 and APR results in the inhibition of GSH synthesis. 37,38,39 Supplementation of 0.5 mM SA results in the substantial increase in ATP sulfurylase, serine acetyl transferase activity and Cys content under salt stress and helps in reversing the effects of NaCl ¡ induced ROS on photosynthesis. This might be due to SA application which helped to protect photosynthesis through increase in ascorbate-glutathione metabolism and sulfur assimilation enzymes, which would enhance the production of glutathione and increase antioxidant enzymes activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The aboveground dry matter under sulfate deprivation treatment was decreased significantly by 62.1%, while SO 4 2-deprivation did not reduce root weight (Figure 2). Globe amaranth shoot growth was affected more than root growth upon SO 4 2-deprivation; more prolonged sulfate deprivation generally results in changes of shoot/root biomass ratio in favor of root production , Yang et al 2003, Buchner et al 2004) and root morphology by increasing the total absorptive surface of the root system (Kutz et al 2002, López-Bucio et al 2003. However, the sulfate-deprived plants seemed to have a rapid growth when they were in bloom; their aboveand underground dry weights were much higher than those of sulfate-supplied plants at the end of flowering sampling on October 31.…”
Section: Growth Statusmentioning
confidence: 99%
“…Up to the early flowering stage, the growth of the plant aboveground part was affected by SO 4 2− deprivation more than root growth, which resulted in a decrease in the shoot/root ratio (Figure 2). That was in coincidence with the previous studies which reported that the prolonged sulfate deprivation Means with the same letter within a column on the same sampling day are not significantly different by the Duncan's Multiple Range Test at P ≤ 0.05 level (r = 3); plus sulfate (plus S), the treatment of sulfate supply in hydroponic culture; minus sulfate (minus S), the treatment of sulfate deprivation in hydroponic culture would generally result in changes of shoot/root biomass ratio in favor of root production , Yang et al 2003, Buchner et al 2004) and root morphology by increasing the total absorptive surface of the root system (Kutz et al 2002, López-Bucio et al 2003. However, at the end of flowering period, all of the three organs weighted significantly more than the corresponding parts of the sulfate-supplied plant when root sulfate deprivation was prolonged (Figure 2).…”
Section: Growth Statusmentioning
confidence: 99%